Sufisme Jawa : Transformasi Tasawuf Islam ke Mistik Jawa - Simuh (Yayasan Bentang Budaya, 1996)
tr, c.1/tr, c.2/ir,c.3/tr c.4/wk, c.5-18/wk, c.19-21/ tr,c.22/ir,c.23/ir,c.24/oen, c.25/ir, c.26-33/tr, c.34